Palliative and end of life care in prisons: a mixed-methods rapid review of the literature from 2014–2018 - McParland, Chris; Johnston, Bridget Margaret (BMJ open, 2019)
ObjectivesTo explore current practice in relation to palliative and end of life care in prisons, and to make recommendations for its future provision.DesignA rapid literature review of studies using qualitative, quantitative and mixed-methods, with a narrative synthesis of results.Data sourcesSix databases searched between January 2014 to December 2018: ASSIA, CINAHL, Embase, MEDLINE, National Criminal Justice Reference Service Abstracts and Scopus.Eligibility criteriaPrimary research articles reporting qualitative or quantitative findings about palliative and end of life care in prisons, published in peer-reviewed, English language journals between January 2014 to December 2018.ParticipantsPrisoners, prisoners’ families, prison healthcare staff and other prison staff.Data extraction/synthesisData extracted included: citation, design, aim, setting, sample/population, methods and key findings. Data were analysed thematically then subject to a narrative synthesis in order to answer the research questions.Quality appraisalTwo researchers independently appraised articles using the Qualsyst tool, by Kmet et al (2004). Aggregate summary quality scores are included with findings. Articles were not excluded based on quality appraisal.Results23 articles were included (16 qualitative, 6 quantitative, 1 mixed methods). Top three findings (by prevalence) were: fostering relationships with people both inside and outside of prison is important to prisoners with palliative and end of life care needs, inmate hospice volunteers are able to build and maintain close relationships with the prisoners they care for and the conflicting priorities of care and custody can have a negative impact on the delivery of palliative and end of life care in prisons.ConclusionsThe key findings are: relationships are important to prisoners at the end of life, inmate hospice volunteers can build close bonds with the prisoners in their care and the prison environment and regime conflicts with best practices in palliative and end of life care. Directions for future research are also identified.PROSPERO registration numberPROSPERO ID: CRD42019118737. Registered January 2019.